Immune modulation, growth performance, and nutrient retention in broiler chickens fed a blend of phytogenic feed additives. (16th October 2018) - Pirgozliev, V; Mansbridge, S C; Rose, S P; Lillehoj, H S; Bravo, D
ABSTRACT: This study aimed to assess the effect of a commercial blend of phytogenic feed additives (PA ), comprising 5% carvacrol, 3% cinnamaldehyde, and 2% capsicum oleoresin on the modulation of immune biomarkers of broiler chickens, their growth performance, dietary energy, and nutrient retention. Four-hundred day-old birds were assigned to one of four dietary treatments. Two control diets based on either wheat (WC ) or maize (MC ) were each given with and without PA at 100 g/t. Growth performance variables including feed intake (FI ), weight gain (WG ), and feed conversion ratio (FCR ) were recorded. Dietary N-corrected apparent metabolizable energy (MEn ), dry matter (DMR ), nitrogen (NR ), and fat retention (FR ) coefficients were also determined. Gene expression of immune biomarkers (cytokines) were determined in caecal tonsil tissue from 21 d old birds. Expression of IL2, IL18, IL10, and IL17C in the caecal tonsils were upregulated ( P < 0.05) in the birds fed MC-based diets compared to the WC fed birds. Feeding PA supplemented diets downregulated the expression of CD40LG ( P < 0.001), IFNG, and IL6 ( P < 0.05). There was a cereal type × PA interaction ( P < 0.05), as expression of IFNB was downregulated in the birds fed PA supplemented MC but not WC. However, expression of IL12B was downregulated in birds fed PA supplemented WC but there was no significant ( P > 0.05) change in expression levels in birds fed MC diets. Feeding MC diets gave greater FI ( P < 0.001) and ME ( P < 0.05), but lower FCR ( P < 0.05) compared to birds fed WC diets. The WG and nutrient retention coefficients were not affected ( P > 0.05) by cereal type. Supplementary PA improved FI ( P < 0.05), WG ( P < 0.001), FCR ( P < 0.05), MEn ( P < 0.05), MEn: GE ratio ( P < 0.05), and FR ( P < 0.05). In conclusion, dietary inclusion of PA improved overall growth performance variables, energy, and nutrient retention and intestinal cytokine expression.